High-altitude vertical wind profile estimation using multirotor vehicles - McConville, Alexander; Richardson, Thomas (Frontiers in Robotics and AI, 2023)
Multirotor vehicles can be significantly affected by the local wind conditions, and due to their under-actuated nature, the response to the flow is clearly visible in the changes in the orientation. From these changes in orientation, wind speed and direction estimates can be determined, allowing accurate estimation with no additional sensors while hovering. In this work we expand on and improve this method of wind speed and direction estimation and incorporate corrections for climbing flight to improve estimation during vertical profiling. These corrections were validated against sonic anemometer data before being used to gather vertical profiles of the wind conditions around Volcan De Fuego in Guatemala up to altitudes of 3000m Above Ground Level (AGL) allowing accurate wind measurements in the region around a highly active volcano frequently producing plumes of ash.